Characteristics of Mackerel Tuna (Euthynnus affinis) Fish Oil During Storage in Freezer - Aulia Andhikawati (JURNAL PERIKANAN DAN KELAUTAN, 2020)
Red flesh fish contain in some varieties of fatty acids. One of the fish that has potential as a source of fish oil is mackerel tuna. The Fatty acid content in mackerel tuna can be used as the source of fatty acid for the human body if that component has been separated from other substances such as water or extracted from fish flesh. The method used to produce oil or fat from the materials suspected to have them is called extraction. While the way of extraction used is wet rendering. This research aims to know the characteristics of omega-3 during storage in the freezer. The Materials used in this research was Mackerel Tuna (Euthynnus affinis). This research was an experimental laboratory with three repetitions. The storage duration consisted of the zero and the thirtieth day. The parameters observed were the amount of yield, a profile of fatty acids, peroxide value, and the test of organoleptic during storage. Analysis data used variety analysis (ANOVA) and advanced test of Tukey HSD. The result data of the organoleptic test was analyzed by Kruskal Wallis test. The result showed that the yield of mackerel fish oil with wet rendering was 0,90% (w/w). There was nine profile of fatty acids consisting of SFA, MUFA, and PUFA. The omega-3 of mackerel tuna fish oil decreases during storage by 5,035% to 3,332%. The peroxide value has been increased from 13,59 meq/kg to 15,45 meq/kg. Organoleptic tests during storage decreased from 5,43 to 5,37. Storage of mackerel tuna fish oil significantly affected the content of fatty acids, peroxide value, and organoleptic value (P<0,05)